Analysis Of Political Party’s Communication Strategy In Increasing Beginner Voter’s Political Participation - Aditya Putra Marzuki (MEDIALOG: Jurnal Ilmu Komunikasi, 2020)
Political participation for young and new voters in Indonesia, particularly in Parepare, is fairly low. This has come in light during simultaneous election in 2019, which was the first election in Indonesia where legislative and executive legislation were held in the same time. Which is why, as a new political party, especially the ones that targetted new voters such as Partai Solidaritas Indonesia (Indonesia’s Solidarity Party) needs to have an innovative and creative political communication strategy to attract the attentions of these new voters. This research analysis identifies these political communication strategy being used by Partai Solidaritas Indonesia branch Parepare, South Sulawesi, in their attempts to increase new voter’s political participation as well to heightened PSI’s vote, whether at the level of communicator, messages, channels, audience, and effect or feedbacks. By using observation and interview methods this research discovered that generally, Partai Solidaritas Indonesia’s attempt to seize significant votes in the 2019’s election were failing, due to several obstraction stems from internal causes as well as external ones. But in particular, the presence of this party has contributed to the increasing political participation of young and new voters in Parepare, South Sulawesi.